PERAN SERTA MASYARAKAT TERHADAP REDUKSI SAMPAH DAN KEBERLANJUTAN SISTEM BANK SAMPAH DI PERUMAHAN GRAHA BUNDER ASRI RW 05 - Ariq Akbar Maulana; Euis Nurul Hidayah; Praditya Sigit Ardisty Sitogasa (Jurusan Teknik Lingkungan, FTM, Universitas Pembangunan Nasional â€œVeteranâ€ Yogyakarta, 2022)
In general, the condition of waste management in the Graha Bunder Asri residential area is still conventional by means of transportation. There is still garbage that is not transported to the final processing site. The community chooses to dump garbage on empty land and burn it. Garbage transportation at the Graha Bunder Asri RW 05 Housing using a garbage cart measuring 150 kg / m3 and a garbage truck measuring 2.5 tons / m3. The waste bank system is a strategy in an effort to invite the community to empower their respective waste before it is disposed of in the final processing site. The study was conducted for 14 days. The results of the analysis were processed using the Correlation Analysis method using the Mini Tab software. The waste that has been sorted by the community at Graha Bunder Asri RW 05 is 7.92 kg / day from the total weight of 30.75 kg / day. The waste that is sorted is food scraps, paper, cardboard, leaves, and plastic bottles. Food waste and leaves are used for composting, while paper, cardboard and plastic bottles are sold to collectors. Meanwhile, reduction waste is transported to the final processing site. At Graha Bunder Asri RW 05, the average volume of waste is 2.67 liters / person / day and the average weight of waste is 0.34 kg / person / day.Â Keywords: Waste Generation, Waste Bank System, Community ParticipationÂ